Developing condensing-frosting performance maps for a variable speed air source heat pump (ASHP) for frosting suppression. (5th July 2022) - Liu, Shengnan; Bai, Xiaoxia; Zhang, Long; Lin, Yao; Deng, Shiming; Wang, Wei; Wei, Minchen
Highlights: Condensing-frosting maps for a variable speed ASHP were developed experimentally. Three experimental outdoor ambient conditions were considered. Variable speed operation affects frosting performance and output heating capacity. Maps can be used to guide frost-free operation of ASHPs at a given heating capacity. Abstract: For a space heating ASHP unit, frosting on its outdoor coil would adversely impact its normal operation, requiring frequent defrosting and resulting in low operating efficiency and poor indoor thermal comfort. It has been shown that varying the speeds of both compressor and outdoor air fan in a variable speed (VS) ASHP unit can lead to different outdoor coil surface temperatures and thus different frosting suppression performances. However, this can also result in different output heating capacities from the ASHP unit. To establish the comprehensive relationship between frosting suppression performances and the total output heating capacity for a VS ASHP unit, an experimental study on developing the condensing-frosting performance maps for a VS experimental ASHP unit under different speed combinations of its compressor and outdoor air fan at three Test Conditions, was carried out and the study results are presented in this paper. The obtained performance maps clearly demonstrated that for the experimental ASHP unit, varying the speeds of its compressor and outdoor air fan would result in not only different outdoor coil surface temperatures, but also different total output heating capacities. A higher outdoor coil surface temperature and thus a better frosting suppression performance may be achieved, but usually at the expenses of losing some of its total output heating capacity. On the other hand, the experimental results also suggested that when the experimental ASHP unit was operated at different speed combinations that can lead to the same or similar total output heating capacities, its operating characteristics in terms of outdoor coil surface states and the total output heating capacity can be remarkably different. The obtained condensing-frosting performance maps may be used as the guidance for the design, operation and control of ASHPs for frost-free operation.